Anak Berkebutuhan Khusus dalam Perspektif Psikologi Pendidikan Islam - Triyono, Agus; Rohimah, Siti (TSAQOFAH, 2026)
Children with special needs (Anak Berkebutuhan Khusus, ABK) are individuals who possess distinct characteristics and learning needs, and therefore require an educational approach that is adaptive, humanistic, and just. This article aims to examine the concept of ABK from the perspective of Islamic Educational Psychology by exploring the integration between educational psychology approaches and Islamic values in the educational process, particularly in Islamic Religious Education (PAI) instruction. This study employs a literature review method by analyzing various relevant sources related to the psychological development of children with special needs, inclusive education, and the principles of Islamic education. The findings show that educational psychology provides a scientific foundation for understanding the cognitive, emotional, social, and behavioral development of ABK, while Islam views ABK as creations of Allah who possess fitrah, dignity, and equal rights to education, with an emphasis on compassion, justice, and aligning education with the child’s abilities. The integration of these two perspectives yields a holistic educational approach that is not only oriented toward academic achievement but also toward strengthening spirituality, shaping moral character, and fostering the independence of children with special needs. Consequently, Islamic Religious Education needs to be designed adaptively through adjustments in content, methods, and evaluation in accordance with students’ needs and capabilities.